THE EVOLUTION OF NATIONAL HEALTH INSURANCE IN INDONESIA: POLICIES, PROGRESS, AND CHALLENGES - Fadhli Zul Fauzi (Jurnal Kebijakan Pemerintahan, 2025)
This research aims to analyze the development of National Health Insurance (NHI) in Indonesia, with every progress and challenges in its evolution. Using a longitudinal case study that enables a nuanced examination of policy processes, shifts, and complexities within their evolving socio-political contexts, this research will explore the dynamics of health insurance policy development over an extended period. Before the establishment of BPJS Kesehatan in 2014, Indonesia’s health insurance landscape was shaped by various schemes targeting different population groups, such as Askes for civil servants, Jamsostek for formal workers, and Jamkesmas for the poor. While these programs expanded access to healthcare, their fragmentation posed challenges to achieving a more inclusive and integrated system. In response, the government initiated a major reform through the establishment of BPJS Kesehatan as part of its commitment to realizing Universal Health Coverage for all citizen. While challenges in resource efficiency and service delivery remain—particularly as BPJS Kesehatan manages far broader coverage than its predecessors—the ongoing reforms reflect Indonesia’s continued commitment to strengthening its health insurance system, improving service quality, and advancing toward Universal Health Coverage through more integrated, accessible, and trusted care. Keywords: Social Protection; Health Policy; National Health Insurance